Ethnomathematics: Exploration of Mathematical Consepts in Batik Udan Liris - Evikasari, Ira; Nurcahyo, Adi; Ishartono, Naufal (Urogram Studi Pendidikan Matematika, Universitas Ivet, 2024)
The purpose of this research is to describe, examine and relate the findings of mathematical concepts in Udan Liris batik in an effort to preserve batik culture in Indonesia. This research uses ethnomathematics theory with a type of qualitative descriptive research method. The data sources in this research are interviews with relevant informants and literature studies from books, journals, articles related to batik. The data in this study were collected through in-depth interviews, observation, and documentation. The data validity checking technique in this research uses source triangulation. Data analysis in this study used an ethnographic approach. Based on the data that has been analyzed, the results of the study found the concept of geometry, algebra, and arithmetic contained in the Batik Udan Liris motif. In the concept of geometry, researchers grouped into three sub-concepts, namely geometric transformations, there are concepts of reflection and translation, plane geometry such as squares, rectangles, rhombuses, triangles, circles, and relationships between lines. While the algebraic sub-concept is used to calculate the results of the arithmetic sequence. And in the arithmetic sub-concept, there is the concept of number patterns in the arithmetic sequence.